Pityriasis versicolor: A clinicomycological and epidemiological study from a tertiary care hospital - Ghosh Sudip; Dey Sunil; Saha Indranil; Barbhuiya Jayasree; Ghosh Arghyaprasun; Roy Aloke (Wolters Kluwer Medknow Publications, 2008)
Background: Pityriasis versicolor is a mild, chronic, usually asymptomatic superficial fungal infection of the stratum corneum, caused by Malassezia yeasts. The purpose of the present study is to assess the clinical profile of a group of patients with pityriasis versicolor and to find out the epidemiological characteristics in this part of India as well as any association, if any, with other diseases. Materials and Methods: For this purpose, 110 consecutive patients of pityriasis versicolor were evaluated clinically and diagnosis was confirmed mycologically at a tertiary care hospital in Kolkata. All data were recorded in a predesigned, pretested semi-structured schedule. The total duration of study period was 12 months. Results: Majority of the patients were young adults. Most of the patients were asymptomatic. There is prominent seasonal variation of the patients with a peak in August and September months. Most of the lesions were hypopigmented scaly macules and were KOH positive. Most commonly involved sites were chest, face and back. Seborrheic dermatitis sometimes coexisted with pityriasis versicolor and a number of patients also had diabetes mellitus and immunosuppressive conditions. Conclusions: Overall, the clinicomycological and epidemiological profile of pityriasis versicolor infection as observed in a tertiary care setting in eastern India does not differ significantly from those observed by previous workers elsewhere.